2016
DOI: 10.4103/0970-0358.191306
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous pedicle propeller flap: An old technique revisited and modified!

Abstract: Background:Post-burn axillary and elbow scar contracture is a challenging problem to the reconstructive surgeon owing to the wide range of abduction and extension that should be achieved, respectively, while treating either of the joint. The aim of this paper is to highlight the use of subcutaneous pedicle propeller flap for the management of post-burn axillary and elbow contractures.Methodology:This is a prospective case study of axillary and elbow contractures managed at a tertiary care hospital using propel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The literature on the use of propeller flaps for post-burn reconstruction is sparse. Hyakusoku et al, 57 Aslaqn et al, 58 and Karki et al 7 have shared their experience mainly with the use of subcutaneous pedicle propeller flaps for post burn reconstruction in various anatomical areas. Generally, it is considered that the local tissue is scarred and not suitable to be elevated as a flap for reconstructing the local area.…”
Section: Applicationsmentioning
confidence: 99%
“…The literature on the use of propeller flaps for post-burn reconstruction is sparse. Hyakusoku et al, 57 Aslaqn et al, 58 and Karki et al 7 have shared their experience mainly with the use of subcutaneous pedicle propeller flaps for post burn reconstruction in various anatomical areas. Generally, it is considered that the local tissue is scarred and not suitable to be elevated as a flap for reconstructing the local area.…”
Section: Applicationsmentioning
confidence: 99%
“…The remaining donor site is covered with skin grafts. Since then, various modifications of the propeller flap design have been described [ 19 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…Karki et al [ 25 ] reported a zig-zag incision around the periphery of the central fossa skin to provide a better esthetic result by interposition of healthy skin in between the skin grafts. This design of subcutaneous pedicled propeller flap is used in type II Kurtzman and Stern axillary [ 41 ], and mild to moderate elbow contractures.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations